2003
DOI: 10.1016/s1472-6483(10)61726-9
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian responses to recombinant FSH or HMG in normogonadotrophic women following pituitary desensitization by a depot GnRH agonist for assisted reproduction

Abstract: At present, there is considerable debate about the utility of supplemental LH in assisted reproduction treatment. In order to explore this, the present authors used a depot gonadotrophin-releasing hormone agonist (GnRHa) protocol combined with recombinant human FSH (rhFSH) or human menopausal gonadotrophin (HMG) in patients undergoing intracytoplasmic sperm injection (ICSI). The response to either rhFSH (75 IU FSH/ampoule; group rhFSH, 25 patients) or HMG (75 IU FSH and 75 IU LH/ampoule; group HMG, 25 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…In a prospective study performed for evaluation of differences in ovarian responses to rFSH and hMG, Balasch et al found mean higher E 2 AUC levels for the patients in the hMG stimulated group (7096 pg/ml vs. 4511 pg/ml), but both oocyte and embryo qualities were lower in this group [27]. It is worth mentioning that both values were higher than the mean levels presented in the study by Levi et al However, the study design did not allow excluding the possibility that the type of gonadotropin preparation influenced oocyte/embryo quality.…”
Section: Discussionmentioning
confidence: 98%
“…In a prospective study performed for evaluation of differences in ovarian responses to rFSH and hMG, Balasch et al found mean higher E 2 AUC levels for the patients in the hMG stimulated group (7096 pg/ml vs. 4511 pg/ml), but both oocyte and embryo qualities were lower in this group [27]. It is worth mentioning that both values were higher than the mean levels presented in the study by Levi et al However, the study design did not allow excluding the possibility that the type of gonadotropin preparation influenced oocyte/embryo quality.…”
Section: Discussionmentioning
confidence: 98%
“…De Placido et al [21] observed that the administration of a daily r-LH resulted in a significant decrease in that cumulative r-FSH amount and in a trend toward a reduction of the stimulation length. Balasch et al [22] reported that with a fixed regimen of 150IU r-FSH or HMG during the first 14 days of treatment, the duration of ovarian stimulation and the per cycle gonadotrophin amount dose were lower in group HMG.…”
Section: Discussionmentioning
confidence: 99%
“…Among infertile patients with hypogonadotropic hypogonadism, the administration of both exogenous LH and FSH are necessary to achieve successful outcomes in assisted reproduction technologies (ART) (4). However, numerous studies have demonstrated successful ART outcomes with the use of recombinant FSHonly protocols (5)(6)(7)(8)(9). Low levels of endogenous LH can persist despite pituitary down-regulation with GnRH analogues (10)(11)(12).…”
mentioning
confidence: 99%